Antimicrobial potential of AH Plus supplemented with bismuth lipophilic nanoparticles on E. faecalis isolated from clinical isolates - Torres Betancourt, Jesús Alejandro; Hernández Delgadillo, René; Flores Treviño, Jorge Jaime; Solís Soto, Juan Manuel; Pineda Aguilar, Nayely; Nakagoshi Cepeda, María Argelia Akemi; Sánchez Nájera, Rosa Isela; Chellam, Shankararaman; Cabral Romero, Claudio (Sage Publishing, 2022)
The objective of this study was to determine the antimicrobial potential of AH plus supplemented with bismuth lipophilic nanoparticles (BisBAL NPs) on the growth of Enterococcus faecalis isolated from patients with endodontic infections. BisBAL NPs, synthesized with the colloidal method, were characterized, in its pure form or AH Plus-absorbed, by energy-dispersive X-ray spectroscopy and scanning electron microscopy (EDS-SEM). Antimicrobial activity was evaluated with disc diffusion assays, and antibiofilm activity with fluorescence microscopy. BisBAL NP-supplemented AH Plus had a 4.9 times higher antimicrobial activity than AH Plus alone ( p = 0.0001). In contrast to AH Plus alone, AH Plus supplemented with BisBAL NP inhibited E. faecalis biofilm formation. The sealing properties of AH plus were not modified by the incorporation of BisBAL NPs, which was demonstrated by a 12-day split-chamber leakage assay with daily inoculation, which was used to evaluate the possible filtration of E. faecalis . Finally, BisBAL NP-supplemented AH plus-BisBAL NPs was not cytotoxic for cultured human gingival fibroblasts. Their viability was 83.7% to 89.9% after a 24-h exposure to AH Plus containing 50 and 10 µM BisBAL NP, respectively. In conclusion, BisBAL NP-supplemented AH Plus constitutes an innovative nanomaterial to prevent re-infection in endodontic patients without cytotoxic effects.